Performance evaluation of three phase induction motor using rotor frame 0.35 mm and 0.50 mm of non-oriented steel sheets - Yanawati Yahya (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2012)
In this project, the three phase AC induction motor have been thoroughly investigated and analyzed in terms of the induction motor parameter, efficiency, power factor and loss segregation. Throughout this project, the performance of the three phase induction motor when it design and modeling by using two (2) different thickness, 0.35 mm and 0.50 mm, of non grain oriented electrical steel sheets with 10 mm rotor bar size. The first part of comparison is done with simulation using FEM Software. The results from FEM Software were compared in terms of power loss, magnetic flux density, eddy current density, torque vs. speed, power loss vs. speed, efficiency vs. speed and power factor vs. speed. The second part is the hardware comparison between two (2) fabricated rotors with sizes of lamination thicknesses 0.35 mm and 0.50 mm respectively.